1961
DOI: 10.1126/science.134.3489.1530
|View full text |Cite
|
Sign up to set email alerts
|

Genetical and Geographic Studies on Isoniazid Inactivation

Abstract: Rapid and slow inactivators of isoniazid are homozygotes, and intermediate inactivators are heterozygotes. There is no dominance between the two alleles. The chasm between Eskimos and Caucasians in isoniazid metabolism is bridged by our investigation of the races in the Far East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(48 citation statements)
references
References 1 publication
3
45
0
Order By: Relevance
“…Such a small value has also been involved in the data reported by other investigators (Jenne, MacDonald & Mendoza, 1961;Ellard, Gammon & Tiitinen, would differ between slow and rapid acetylators (Weber & Hein, 1979 In this case it is probably suggested that the hydralazine administration was causally correlated to the aetiology of the development of peripheral neuropathy according to the definition of cause-effect relationship between a drug and its adverse reaction proposed by Karch & Lasagna (1975). This is the first report in a slow acetylator residing in the region where rapid acetylators highly predominate in general population (Sunahara et al, 1961;Lunde et al, 1977;Weber & Hein, 1979). This was not unexpected as has been suggested by other investigators (Lunde et al, 1977) that slow acetylators are more prone to develop INH-induced peripheral neuropathy.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Such a small value has also been involved in the data reported by other investigators (Jenne, MacDonald & Mendoza, 1961;Ellard, Gammon & Tiitinen, would differ between slow and rapid acetylators (Weber & Hein, 1979 In this case it is probably suggested that the hydralazine administration was causally correlated to the aetiology of the development of peripheral neuropathy according to the definition of cause-effect relationship between a drug and its adverse reaction proposed by Karch & Lasagna (1975). This is the first report in a slow acetylator residing in the region where rapid acetylators highly predominate in general population (Sunahara et al, 1961;Lunde et al, 1977;Weber & Hein, 1979). This was not unexpected as has been suggested by other investigators (Lunde et al, 1977) that slow acetylators are more prone to develop INH-induced peripheral neuropathy.…”
supporting
confidence: 52%
“…However, the distribution of genetic acetylation phenotypes of Japanese is very different from that of Caucasians. Approximately 50% or more of Caucasians are slow acetylators (Lunde, Frislid & Hansteen, 1977), whereas as much as 88.5% of the Japanese population are rapid acetylators (Sunahara et al, 1961;Lunde et al, 1977). We assume that this distribution difference of acetylation phenotypes between Japan and other countries would be related to the discrepancy of the incidence of adverse reactions induced by drugs as substrates for N-acetyltransferase.…”
mentioning
confidence: 99%
“…Compared with Caucasians where 40 to 50% are rapid acetylators, as much as 90% of the Japanese belong to the rapid acetylator phenotype (Sunahara et al, 1961). The frequency of PMs of mephenytoin wag reported to be 18% (Nakamura et al, 1985) and 22.6% (Jurima et al, 1985) in a Japanese population, whereas it was 2.7% in a white American (Nakamura et al, 1985) and 4.2% (Jurima et al, 1985) in a Canadian population.…”
Section: Discussionmentioning
confidence: 92%
“…The chi-square method was done to compare the acetylator distribution data between the two groups of this study and between these two groups with those reported for the Japanese population by Sunahara et a1 (18). The betatype possible error or the power (29,30) was also estimated.…”
Section: Methodsmentioning
confidence: 99%